PENGEMBANGAN LKPD BERBASIS KONTEKSTUAL PADA PEMBELAJARAN TEMATIK TEMA 3 TUGASKU SEHARI-HARI DI KELAS II SD - Nur Fika Indriyani; Sukmawarti Sukmawarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to: (1) Develop contextual-based LKPD on Thematic Learning Theme 3 My Daily Tasks in Class II Elementary School. (2) To determine the feasibility of contextual-based LKPD in Thematic Learning Theme 3 My Daily Tasks in Grade II Elementary School. From the results of feasibility validation by material experts, media experts and learning experts. This research is a type of research and development with reference to Thiagarajan's 4D model, namely Define, Design, Development, Disseminate. The instrument used to collect data was a questionnaire. The data analysis technique is descriptive qualitative. Based on the teacher response research data, it can be seen that the quality of the student worksheet media (LKPD) on the theme of my daily tasks obtained a percentage of 91%. Based on the assessment of media experts, they obtained 78% of 10 statements. Based on the material expert assessment, they scored 94% of 10 statements. The Student Worksheet (LKPD) developed with the theme of my daily tasks is very valid and can be applied as a first step in the teaching and learning process at school